KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT TERHADAP ISU KAWASAN ARKTIK ERA OBAMA II DAN TRUMP - Lula Lasminingrat, Lula (2022)
The Arctic Region is a regional area that surrounds the Arctic Sea and consists of 8 countries namely the United States via Alaska, Canada, Russia, Denmark via Greenland, Norway, Iceland, Sweden, and Finland. The Arctic region is undergoing unpredictable changes both environmentally and geopolitically due to the process of melting ice along with the impact of climate change. The process of melting ice in the Arctic has made areas that were previously isolated and far from human reach, have now developed into strategic and crucial areas for Arctic and non-Arctic countries, including the United States (US). The Arctic region is estimated to hold oil and gas reserves that have never been explored by humans, along with the potential for extension of the territorial sea area on the basis of the Continental Shelf, to new alternative shipping routes, namely the Northwest Passage in Canada and the Northern Sea Route in Russia. Since gaining legitimacy in the Arctic through the 1867 purchase of Alaska from Russia, the United States has issued several policy documents to respond to shifting situations and conditions in the region. The US issued the 2013 National Strategy for the Arctic Region (NSAR-2013) in the Obama II era and the 2016 Department of Defense Arctic Strategy (DOD 2016) and the 2019 Department of Defense Arctic Strategy (DOD 2019) in the Trump era. Obama II's policy of declaring the US as an Arctic country is characterized by cooperation, the role of institutions, diplomacy, as well as overcoming environmental issues. On the other hand, Trump's policy sees the Arctic as an arena of strategic competition by bypassing the role of institutions, increasing military capabilities, to his views on environmental issues that are not his policy priorities in the region. There is a gap between the goals of US foreign policy in the Arctic in providing an active presence and its implementation in a region that lags far behind other countries, especially Russia in terms of military capabilities. This qualitative case study research uses maritime power theory to understand how the US should dominate the Arctic Sea and an adaptive foreign policy model in analyzing the differences in US foreign policy in the Arctic. There are factors that determine differences in Arctic-US foreign policy, namely the use of Arctic Council instruments and military capabilities, perceptions of climate change, internal government and domestic conditions, and perspectives on the activities of China and Russia.